Biophysics of Nucleic Acids Celebrating the 75th Birthday of Professor Kenneth J. Breslauer - Chalikian, Tigran; Völker, Jens (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue comprises 15 papers broadly outlining current trends in nucleic acid biophysics. It contains original research papers and reviews on structure, stability, and interactions of canonical and non-canonical nucleic acids. The authors describe the use of established, time-honored experimental and computational techniques as well as their more recently developed counterparts. Molecular insights that can be gained from the papers collected in this issue range from the fundamental to the applied with emphasis on biological functions and biomedical prospects of nucleic acids. The collection is not meant to be exhaustive, but to highlight recent advances from select laboratories worldwide. Nevertheless, it represents a useful guide for scientists who wish to familiarize themselves with biophysical topics in nucleic acid research. This Special Issue will be useful both for researchers who study fundamental aspects of nucleic acid structure, stability, and dynamics, as well as for those that are mainly interested in practical biological and biomedical applications of nucleic acids.